Pengembangan Media Game Ludo Dan Link (GAUL) Untuk Meningkatkan Hasil Belajar Kognitif Siswa Sekolah Dasar Pada Era Pandemi Covid-19 - Wardhani, Dyah Ayu Pramoda; Mauliddiyah, I’in Cahya (Primary Education Journals (Jurnal Ke-SD-An), 2023)
The transition from online learning to face-to-face learning is limited, resulting in a decrease in student learning outcomes by 55%, as well as causing various other impacts. The purpose of face-to-face learning is limited to making it easier for students to understand face-to-face learning, which was previously done online which was deemed less effective in understanding learning. One solution that can be used is the use of learning media. The approach in this study uses a qualitative approach, with Research and Development (R&D) research methods with the ADDIE development model. GAUL learning media has been validated by getting very good qualifications. Media GAUL has been tested for eligibility with very decent qualifications. The percentage can increase learning outcomes as much as 88%, so that the GAUL media is feasible and can improve the learning outcomes of grade 2 elementary school students.